Migrants and refugees in Europe: acceptation, integration and crime prevention - Rodrigues, Carlos (2022)
Global migration is a reality of the Humanity, due the most different reasons, but within specific legal frameworks – each State and International Law, representing different position and possibilities to the human beings as by the political, social, economic, and cultural powers. This research is focused on the global migration and refugees, within the international legal definition. If there are States and regions where these human beings are welcome, accepted, and integrated, not only by the legal context but by the governments, societies, and economy. Since the Arab Spring, the reality for millions of Refugees is dramatic by the violation of the Human Rights, the International Law, and States Fundamental Rights. There are a controverse Public Opinion provoking the discrimination, rejection, and violence against these Human Beings, creating such negative conditions that conduct millions to the abandonment or even death. There are different international movements, involving International organized crime acting with Migrants and Refugees – human trafficking, smuggling, exploitations, violence, and all kind of violations. The International Security – legal, protection and criminal (re)action, police authorities – between States and International Organizations have developed different reactions. This is a serious and difficult problem needing a permanent effective work of all structures to protect millions of Human beings. The European Union, working together the international community, as well as with the most different movements – public and/or private – need to develop a concerted and strategic work receiving and integrating the Refugees, which measures must cover and protect all in Europe, regardless their origin.